Analisis Bauran Pemasaran Digital untuk Meningkatkan Penjualan pada Usaha Songket Aina di Kecamatan Silungkang Kota Sawahlunto - Tessa Mardianti; Rusydi Fauzan (Lembaga Yasin AlSys, 2026)
The digital marketing mix in songket businesses has become a focus in various previous studies; however, research that specifically discusses the optimization of the 7P digital marketing mix in increasing sales at the Songket AINA Silungkang business remains limited. This study aims to analyze the implementation of the 7P digital marketing mix in increasing sales at the Songket AINA business in Silungkang Subdistrict, Sawahlunto City. This study employed a qualitative approach with a case study design, involving 11 participants selected through the purposive sampling technique. Data were collected through interviews, observation, and documentation and were then analyzed using interactive analysis techniques through the stages of data reduction, data presentation, and conclusion drawing. The results show that the product and place variables have high performance, whereas promotion, process, people, price, and physical evidence are in the low category, which affects sales fluctuations throughout 2024. These findings contribute to the development of studies on the 7P marketing mix in the digital context and broaden understanding of marketing strategies in locally culture-based MSMEs. The conclusion of the study emphasizes that the integration of all elements of the digital marketing mix is important for increasing sales more stably and sustainably. The practical implication is that business actors need to optimize digital promotion, improve human resource capacity, and enhance operational processes so that marketing strategies are more adaptive to market dynamics.